Terracidiphilus gabretensis gen. nov., sp. nov., an Abundant and Active Forest Soil Acidobacterium Important in Organic Matter Transformation - García-Fraile, Paula; Benada, Oldrich; Cajthaml, Tomáš; Baldrian, Petr; Lladó, Salvador (Applied and environmental microbiology, 2016)
Understanding the activity of bacteria in coniferous forests is highly important, due to the role of these environments as a global carbon sink. In a study of the microbial biodiversity of montane coniferous forest soil in the Bohemian Forest National Park (Czech Republic), we succeeded in isolating bacterial strain S55(T), which belongs to one of the most abundant operational taxonomic units (OTUs) in active bacterial populations, according to the analysis of RNA-derived 16S rRNA amplicons. The 16S rRNA gene sequence analysis showed that the species most closely related to strain S55(T) include Bryocella elongata SN10(T) (95.4% identity), Acidicapsa ligni WH120(T) (95.2% identity), and Telmatobacter bradus TPB6017(T) (95.0% identity), revealing that strain S55(T) should be classified within the phylum Acidobacteria, subdivision 1. Strain S55(T) is a rod-like bacterium that grows at acidic pH (3 to 6). Its phylogenetic, genotypic, phenotypic, and chemotaxonomic characteristics indicate that strain S55(T) corresponds to a new genus within the phylum Acidobacteria; thus, we propose the name Terracidiphilus gabretensis gen. nov., sp. nov. (strain S55(T) = NBRC 111238(T) = CECT 8791(T)). This strain produces extracellular enzymes implicated in the degradation of plant-derived biopolymers. Moreover, analysis of the genome sequence of strain S55(T) also reveals the presence of enzymatic machinery required for organic matter decomposition. Soil metatranscriptomic analyses found 132 genes from strain S55(T) being expressed in the forest soil, especially during winter. Our results suggest an important contribution of T. gabretensis S55(T) in the carbon cycle in the Picea abies coniferous forest.
Keywords: rostliny; půdní mikrobiologie; Plants; Biodegradation, Environmental; Biotransformation; Forests; Phylogeny; Molecular Sequence Data; molekulární sekvence - údaje; biodegradace; fylogeneze; biotransformace; Acidobacteria; Soil Microbiology; lesy